Evidence for tidal triggering of high‐amplitude rapid tremor reversals and tremor streaks in northern Cascadia. Issue 16 (27th August 2013) - Thomas, Trevor W.; Vidale, John E.; Houston, Heidi; Creager, Kenneth C.; Sweet, Justin R.; Ghosh, Abhijit
Abstract : [1] We provide a new link between tectonic tremor propagation, tremor amplitude, and tidal stresses by analyzing high‐resolution tremor locations and amplitudes determined by multibeam backprojection of data from an array of subarrays. For two Cascadia episodic tremor and slip events, we observe repeating, high‐amplitude rapid tremor reversals (RTRs) and tremor streaks. They tend to occur when tremor amplitudes are highest and occur almost exclusively during periods of thrust‐encouraging, tidally induced shear stress on the fault. We speculate that thrust‐encouraging shear stress from tidal loading forces trigger RTRs and streaks that energetically rerupture the weakened fault behind the slow slip front. The high rate and amplitude of tremor during RTRs and streaks stands in contrast to the hypothesis that activity at the leading edge of the slow slip zone is the most energetic and loudest. This implies that the spatiotemportal pattern of slow earthquake slip migration is even more intricate than previously reported. Key Points: RTR's and streaks are high in amplitude relative to tremor at the slip front RTR's and streaks occur during slip‐encouraging tidal shear stress RTR's and streaks may be triggered by tidal loading and tidal stresses